Trends and Implementation of Electric Vehicle Ecosystem in Indonesia: A Literature Study - Humayro, Afifah; Virgianita, Asra (Hasanuddin University, 2024)
This research discusses the implementation of the electric vehicle ecosystem in Indonesia as one of the steps to support the goals stated in the Paris Agreement, namely achieving net zero emissions (NZE) by 2060. Indonesia is one of the countries that implements electric vehicles to achieve NZE. However, Indonesia's technology is not yet established for producing electric vehicles and distributing them to the global market. Therefore, this research was motivated to look at 20 sources of literature that have discussed cooperative relations in the Indonesian automotive industry sector with electric vehicle-producing countries. This research maps this literature using a taxonomy method in three main topics, namely (1) the development of the transportation and automotive sector in Indonesia, (2) China, South Korea, and Japan as cooperation partners in the electric vehicle industry, (3) the readiness of electric vehicle ecosystem implementation in Indonesia. This research also includes the explanation of national interest theory to see the perspective of international relations in the purpose of the Indonesia government in achieving electric vehicle ecosystem.